Makam Tradisional Etnis Cina di Kota Ambon - Cheviano E. Alputila (Kapata Arkeologi, 2016)
Ethnic Chinese have a long history around the world. As a people renowned for their versatility in the trade, this community can be found anywhere. Ambon city is one of the many areas in the past inhabited by the ethnic Chinese community. Evidence of their existence in the past in Ambon today can be observed from traditional Chinese tombs are scattered in several locations. In addition to functioning as an initial step in the record of its existence this paper serves to reveal the importance of the existence of traditional Chinese tomb in the city of Ambon. The method used is a survey, interviews, and literature review. From the survey results it is known that the traditional Chinese grave condition as a whole in the city of Ambon was on the verge of collapse and require serious attention of all parties. Loyalty to the ancestral customs of the people of China still run by the Chinese community in the city of Ambon. This is reflected in the traditional Chinese tomb suitability components in common with traditional Chinese tomb in the city of Ambon.